2021
DOI: 10.1038/s41598-020-80134-2
|View full text |Cite
|
Sign up to set email alerts
|

THz guided-mode resonance notch filter with variable filtering strength

Abstract: In this paper, we propose a terahertz (THz) guided-mode resonance (GMR) notch filter made of a monolithic polyethylene terephthalate (PET) film, which has a monolayer grating structure. The proposed configuration shows both polarization-dependent and polarization-independent notch filter characteristics for the incident THz wave depending on the rotation angle of the second grating film. When the rotation angle is 0°, the filtering strength (transmittance) at resonance frequency changes from 0.4 (0.996) to 99.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, Yuan et al 43 presented a photonic filter employable at the absorption band of acetylene gas. Others include terahertz 44 , infrared 45 , microwave 46 , 47 and commercial ultra-violet filters. These hold potential for phase imaging across the spectrum using the methods outlined in this paper, with applications in machine vision and biological imaging beyond the visible range.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yuan et al 43 presented a photonic filter employable at the absorption band of acetylene gas. Others include terahertz 44 , infrared 45 , microwave 46 , 47 and commercial ultra-violet filters. These hold potential for phase imaging across the spectrum using the methods outlined in this paper, with applications in machine vision and biological imaging beyond the visible range.…”
Section: Discussionmentioning
confidence: 99%
“…Metals show considerable Ohmic loss beyond the microwave frequencies, while dielectric metasurfaces as a platform perform lower levels of dissipation [32]. Bark et al proposed an all-dielectric THz GMR filter through one-dimensional (1D) grating for the first time [33], and then realized tunable THz filters [34], notch filters [35], and polarization-independent filters [36]. Han et al experimentally demonstrated high-Q THz GMRs in siliconbased 2D metasurfaces [37].…”
Section: Introductionmentioning
confidence: 99%
“…The independence of the filter regarding the polarization of the incident beam is a vital element not only for optical systems and devices but also for THz applications. The abovementioned notch filters can be implemented as polarizationindependent and polarization-dependent THz filters by controlling the relative rotation angles of cascading two identical 1D grating structures [35]. And the Bark proposed polarizationindependent filters were designed by adjusting the filling factor and grating thickness [36] .…”
Section: Introductionmentioning
confidence: 99%